Preparation of Graphene-Like Porous Carbons With Enhanced Thermal Conductivities From Lignin Nano-particles by Combining Hydrothermal Carbonization and Pyrolysis - Dong, Huiling; Li, Min; Jin, Yongcan; Wu, Yan; Huang, Caoxing; Yang, Jinlai (Frontiers in Energy Research, 2020)
Lignin nano-particles (LNPs) exhibit properties that distinguish them from the production of other lignin-based materials. However, little research has been performed to investigate whether porous carbons produced from LNPs exhibit a performance superior to those derived from untreated lignin. In this study, lignin was fabricated into LNPs and used to prepare high-performance porous carbons with enhanced thermal conductivities compared to that of carbons from neat lignin. Two different preparation protocols were employed: direct pyrolysis and hydrothermal carbonization followed by pyrolysis. Carbons obtained from 100 to 300 nm LNPs possessed more graphene-like structures than carbons from unaltered lignin. In addition, carbons prepared using a combination of hydrothermal carbonization and pyrolysis exhibited higher specific surface areas (108.81–220.75 m2/g) and total pore volumes (0.098–0.166 cm3/g) than those prepared via direct pyrolysis. In addition, LNP-derived carbons exhibited superior thermal conductivities (0.45 W/mK) and thermal conductivity rates (0.51°C/s). This work provides the useful finding that superior graphene-like porous carbons can be produced by transforming lignin into LNP and then hydrothermally carbonizing the resulting material prior to pyrolysis.